Evaluating The Stability Of Parallel Rock Discontinuities Along Al-Mishar Road In The Bir Al-Ghanam Area (NW Libya). - Alakhdar أبوالقاسم (Journal of Pure & Applied Sciences, 2023)
Parallel slopes along Al-Mishar road were excavated as part of a road expansion project. This excavation revealed rock discontinuities consisting of rock debris. Repeated visits to the area of Bir Al-Ghanam indicated collapses occurring at specific locations where these rock discontinuities were exposed. The main research problem lies in understanding the underlying causes of these collapses, which originate from the rock discontinuities within gypsum rocks. Failure to comprehend these causes may lead to future collapses with potentially disastrous consequences for road users. Therefore, the overall objective of this study was to assess the stability of the rock discontinuities using a combination of field investigations and laboratory analyses. This involved evaluating internal cohesion values, friction angles, and simulating slope stability using RocPlane software. Two significant variables were examined: the variation in water content and the slope inclination angle. Stability values of the rock discontinuities were calculated under three different internal saturation conditions (natural, with 30mm of water, and 50 mm of water). Additionally, the study investigated the impact of changing the slope inclination angle from the natural angle of 35 degrees to a cutting angle of 80 degrees. The key findings revealed that the internal cohesion decreased from 8.3 t/m² at 9.9% saturation to 5.2 t/m² at 16% saturation, indicating the influence of internal water saturation on reducing the cohesion of slope components. Furthermore, the study showed that the slope remained stable at an inclination angle of 35 degrees, while collapse occurred at the cutting angle of 80 degrees, where the driving force prevailed and the resisting force was absent, resulting in a safety factor of 0. Based on the study's outcomes, it is recommended to simulate the natural conditions affecting the slope before initiating slope cutting operations.